Erythema ab igne as a side effect of working in a flower shop – case report and literature review - Jaworek, Andrzej K.; Jaworek, Magdalena; Jelonek, Iga; Mleczko, Mateusz; Wojas-Pelc, Anna (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction . Erythema ab igne (EAI) is a rare skin disease (since the common use of central heating) characterized by reticular, erythematous and hyperpigmented patches resulting from chronic exposure to infrared radiation. Although the condition is generally benign, chronic heat exposure can induce dysplasia and, rarely, squamous cell carcinoma. The pathogenesis of the disease is not yet fully understood. Objective . Presentation of the diagnostic and therapeutic difficulties in a patient with EAI. Case report. The patient had erythema ab igne that developed on the shins, due to the effect of a heating device used in the flower shop. The clinical presentation, differential diagnosis and available treatment options of the disease are described. Conclusions . Erythema ab igne is a rare skin disease, but there is a need for special oncological observation of these patients.